Peran Inisiatif Global Gateway Uni Eropa Terhadap Perkembangan Infrastruktur Di Mozambik 2021-2024 - Chika Raka Siwi; Yanuar Rahmadan (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The Global Gateway initiative is a European Union strategy launched in 2021 to strengthen global connectivity through investment in sustainable and high-quality infrastructure. Mozambique is one of the EU partner countries in Southern Africa receiving support from this initiative, particularly in the transport sector. This study analyzes the role of the EU Global Gateway in supporting infrastructure development in Mozambique during 2021-2024. The research applies a qualitative descriptive method through a case study approach, usang literature review of EU official documents, European External Action Service publications, international development reports, and relevant academic articles. The findings indicate that Global Gateway contributes to improving transport connectivity through three main channels: modernizing the Maputo-Ressano Garcia railway line, upgrading key road corridors such as Nacala and Mueda-Negomano, and strengthening regional trade links with neighbouring countries. These projects are projected to increase rail freight capacity, reduce logistics bottlenecks, shift freight movement from road to rail, and support lower carbon emissions. However, implementation still faces challenges related to financing sustainability, coordination among Team Europe actors, climate vulnerability, security conditions in northern Mozambique, and competition with other infrastructure initiatives such as China’s Belt and Road Initiative. Therefore, Global Gateway is not merely a development assistance program, but also a strategic instrumen for the EU to consolidate its role as an international actor in Africa while supporting Mozambique’s regional integration.